Endocarditis due to Gram Positive Anaerobic Cocci: First report of Peptoniphilus indolicus endocarditis and literature review. (July 2021) - Lourtet-Hascoet, Julie; Hascoet, Sébastien; Galinier, Jean-Louis; Fontenel, Benoît; Monteil, Benoît; Bonnet, Eric
Highlights: Gram positive anaerobes are involved in less than 1% of Infective Endocarditis (IE). We reported the first case of P. indolicus IE after transcatheter valve replacement. All reported cases of anaerobic bacteria IE were reviewed. These IE occur on prosthetic valves and induce rare complications. Compared to streptococci, these IE are associated to favorable outcome of patients. Abstract: Background: Gram positive anaerobic cocci (GPAC) are rare causes of Infective Endocarditis (IE). We report the first case of Peptinophilus indolicus endocarditis 2 months after valve replacement. We reviewed all cases of GPAC IE listed in PubMed and identified main characteristics of these infections. Case report: A 82-year old man presented a 48H fever with transcatheter valve replacement 2 months earlier. Hyperleukocytosis and high C-Reactive protein level were found. Gram positive cocci grew on anaerobic blood cultures. Peptoniphilus indolicus was identified, susceptible to Penicillin G (MIC < 0.25 mg/L). Transesophageal echocardiography showed a large vegetation. Cardiac tomography confirmed a hypodense formation. Ceftriaxone IV was prescribed followed by amoxicillin for 6 weeks. The outcome was favorable and after 8 months, the patient presented no fever and normal blood test. The last TOE didn't show any defect. Results: P. indolicus are Gram Positive Anaerobic Cocci (GPAC) bacteria described in deep infections. In this case, IE occurred early after intervention without any secondary embolic complication. We reviewed 34 cases reports-series of GPAC IE. They are more often observed in male patients with mean age of 52 years and occur mainly on prosthetic valve. GPAC are described as susceptible bacteria towards antibiotics. Penicillin G, amoxicillin are first-choice molecules with 6 weeks duration of treatment. We compared GPAC to streptococcal and anaerobic Gram-Positive Bacilli (GPAB) IE. Anaerobic IE occur more often on prosthetic valves compared with streptococci IE. Surgical treatment was more frequently performed in anaerobic IE than in streptococci IE. Amoxicillin MIC was lower for anaerobic compared with streptococci IE. A lower mortality rate seems to be observed with GPAC than streptococci IE. Conclusion: We reported the first case of Peptoniphilus indolicus IE. These GPAC IE occur mostly on prosthetic valves without embolic complications, are susceptible to antibiotics and lead to frequent favorable outcome of the patients.